Post-bariatric body contouring: our experience - Grieco, Michele; Grignaffini, Eugenio; Simonacci, Francesco; Di Mascio, Donatello; Raposio, Edoardo (Acta Biomedica Atenei Parmensis, 2016)
Obesity is a growing socio-economic problem especially in the western population. Patients who are undergoing bariatric surgery after a significant weight loss have an altered body profile which may have an important psychological impact. These patients may be candidates for surgical body-lifting. The aim of body-lifting is to obtain a firmer, tighter, rejuvenated appearance for patients who have lax, ptotic tissues. In this paper we describe our experience with two techniques currently practiced by our team, brachioplasty and thigh lift, reporting the indications, the surgical technique and possible complications